Asian rainfall anomaly patterns associated with interannual variations of early and peak summer rainfall over the Indochina Peninsula. (6th May 2022) - Shi, Yu; Wu, Renguang; Kripalani, Ramesh; Zhu, Peijun
Abstract: This study investigates the rainfall anomaly patterns over Asia associated with interannual variations of early summer (May–June) and peak summer (July–August) Indochina Peninsula (ICP) rainfall during 1979–2016. It is found that the early and peak summer rainfall variation in the ICP displays an out‐of‐phase relation to that in central Asia and central China, respectively. Analysis reveals that the out‐of‐phase early summer rainfall variation between the ICP and central Asia tends to occur in ENSO decaying years and the out‐of‐phase peak summer rainfall variation between the ICP and central China tends to occur in ENSO developing years. The early summer out‐of‐phase rainfall anomaly pattern between the ICP and central Asia forms due to a Rossby wave type response to anomalous heating extending from the ICP to northeast India, which is attributed to a combined influence of same sign sea surface temperature (SST) anomalies in the equatorial eastern Pacific and tropical southwestern Indian Ocean and opposite sign SST anomalies in the tropical western North Pacific. The peak summer out‐of‐phase rainfall variation between the ICP and central China forms due to a meridional atmospheric circulation pattern over East Asia and the western North Pacific, which is resulted from the combined impacts of opposite SST anomalies in the equatorial central Pacific and tropical southeastern Indian Ocean. Further analysis indicates that the out‐of‐phase rainfall variations between the ICP and central Asia in early summer and between the ICP and central China in peak summer may occur without anomalous tropical Indo‐Pacific SST forcing. Abstract : The spatial pattern of interannual rainfall anomalies over Asia associated with the Indochina Peninsula (ICP) rainfall variation is different in early summer (May–June) and peak summer (July–August). Early summer rainfall displays an out‐of‐phase variation in the ICP and central Asia. Peak summer rainfall displays an out‐of‐phase variation in the ICP and central China.